Comparison of Physical Activity Levels by Sex in Public Elementary Schools and Private Elementary Schools - Wulan Rahmadona; Wulandari Putri; Lukmannul Haqim Lubay (Jurnal Indonesia Sosial Teknologi, 2024)
In the development process of primary school students, physical activity plays an important role in supporting this development. Several factors, including school type and student gender, can cause differences in physical activity levels. This study sought to review how physical activity levels are based on school type and how physical activity levels differ between male and female students in public and private primary schools. This study was conducted in Purwakarta Regency, Wanayasa District, and took a population of 3 public and three private elementary schools, with a sample of 60 people. This type of research is descriptive quantitative and uses the Physical Activity Questionnaire for Older Children (PAQ-C) research instrument. From the results of the study, it is known that public primary schools have better physical activity levels compared to private primary schools. Male and female students in public primary schools have better physical activity levels than private primary school students.